Content Visualization: An Evaluation of PowerPoint Effectiveness as a Learning Tool for Students - Pratami, Devi; Amalia Nur Fajrillah, Asti; Fabrianti Kusumasari, Tien (International Journal of Engineering and Technology, 2018)
PowerPoint is a slide show presentation program from Microsoft, which also one of the most widely used programs to develop visual presentation all over the world. PowerPoint has become enormously popular because of the functionalities offered and since it is designed to be easy to use. Previous researchers stated PowerPoint as one of the best tool to facilitate users to deliver idea/objective/goal, especially in education field. But some of the researchers argue that in todayâ€™s environment, PowerPoint no longer be the best tool to deliver information. This research aims to evaluate and design the content of the slide which influences the level of students understanding on information being presented. This research will be comparing three methods at once, which are a conventional method where the material course will be presented without any PowerPoint and are limited to boards and books. The second method will be a material-course presentation using a PowerPoint where it was using an aesthetically pleasing and methodically correct PowerPoint. And the last method would be the combination between the two. By using a statistical test ANOVA that among three methods there is no significance impact to the students understanding. Nevertheless, based on the test score that are done after treatment the results show that the quality of PowerPoint slide has an influence to the level of students understanding compared to conventional methods (blackboard and textbook). But only attractive slide itself is insufficient to improve students understanding, this study will incorporate conventional method and attractive slide through content visualization in order to gives a better impact on students understanding.Â Â